(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the current status of treatment adherence among outpatients with type 2 diabetes mellitus at the General Outpatient Department, Traditional Medicine Institute, in 2025, and to identify some related factors Subjects and methodology: A descriptive cross-sectional study was conducted on 380 patients diagnosed with type 2 diabetes who were receiving outpatient treatment at the Outpatient Department, Institute of Traditional Medicine, Ho Chi Minh city from March 2025 to May 2025. Data were collected using a questionnaire and assessed on 4 aspects of patient adherence: nutrition, medication use, physical activity, blood sugar monitoring and periodic re-examination. Result: The overall treatment adherence rate among patients was 51.3%. Among the components, medication adherence was the highest at 79.7%, followed by dietary adherence at 61.8%, adherence to blood glucose monitoring and regular check-ups at 58.7%, while physical exercise adherence was the lowest at 52.9%. Five factors were found to be significantly associated with treatment adherence: gender, education level, living situation (living with relatives), distance to the hospital, and complication status. All factors regarding family reminders showed a strong and statistically significant association with treatment adherence. Conclusion: The treatment adherence level among outpatients with type 2 diabetes mellitus at the Traditional Medicine Institute, Ho Chi Minh city was only about 50%. Effective interventions are needed to improve treatment adherence in this patient group in order to better control blood glucose levels and prevent diabetes-related complications.